고등학교의 남녀공학 여부가 대입수능에 미치는 영향 - 김범수 (14088, 2015)
Park et al. (2012) examined the impacts of coeducation in high school on the college scholastic ability test using random assignment in Seoul high schools. However, the student random assignment in Seoul within a school district was performed only within